Investigation of the Shear Flow Effect and Tip Clearance on a Low Speed Axial Flow Compressor Cascade - Mahesh Varpe; A. M. Pradeep (International Journal of Rotating Machinery, 2013)
This paper explores the effect of inlet shear flow on the tip leakage flow in an axial flow compressor cascade. A flow with a high shear rate is generated in the test section of an open circuit cascade wind tunnel by using a combination of screens with a prescribed solidity. It is observed that a stable shear flow of shear rate 1.33 is possible and has a gradual decay rate until 15 times the height of the shear flow generator downstream. The computational results obtained agree well with the available experimental data on the baseline configuration. The detailed numerical analysis shows that the tip clearance improves the blade loading near the tip through the promotion of favorable incidence by the tip leakage flow. The tip clearance shifts the centre of pressure on the blade surface towards the tip. It, however, has no effect on the distribution of end wall loss and deviation angle along the span up to 60% from the hub. In the presence of a shear inflow, the end wall effects are considerable. On the other hand, with a shear inflow, the effects of tip leakage flow are observed to be partly suppressed. The shear flow reduces the tip leakage losses substantially in terms of kinetic energy associated with it.